Perkembangan Pendidikan Islam di Madrasah: Analisis Historis, Dinamika Kebijakan, dan Transformasi Pendidikan di Indonesia - Listi Hani Siregar; Abdusima Nasution (Yayasan Mutiara Hati Moeslem, 2026)
The development of Islamic education in madrasas has become an important part of the educational system in Indonesia. Previous studies have examined the historical development, educational policies, and curriculum transformation of madrasas. However, these studies generally focus on specific aspects and have not comprehensively explained the relationship between historical development, educational policies, curriculum transformation, and contemporary challenges that influence the development of madrasas. This study aims to analyze the development of Islamic education in madrasas from a historical perspective and to identify the factors that have contributed to their development within the Indonesian national education system. This study employed a library research method using a historical-analytical approach. The data were collected from scholarly books, journal articles, government policy documents, and other relevant academic sources, and were analyzed through content analysis. The findings indicate that the development of madrasas has been influenced by their ability to integrate Islamic education with general education, supported by government policies, curriculum transformation, and active community participation. These factors have enabled madrasas to develop more rapidly than many other Islamic educational institutions while maintaining their Islamic identity. The novelty of this study lies in its comprehensive analysis that integrates historical development, educational policies, curriculum transformation, and the dynamics of madrasa development within a single analytical framework. This study contributes to the advancement of Islamic education studies by providing a broader understanding of the factors shaping the development of madrasas as adaptive Islamic educational institutions within the national education system.